Alabaos y conflicto armado en el Chocó: noticias de supervivencia y reinvención (Encuentros, 2017)
This article is an initial approach to the effects of the armed conflict on the alabaos chants, a musical and ritual practice of the afrocolombian communities on the Pacific region of the country. In the first part, the document explains the presence of the armed conflict in the region of the upper basin of the San Juan river (Chocó), as a latent menace that makes risky to learn and practice the chants, on a traditional ritual context. The second part explores the capacity to reinvent itself as a denunciation music, with a role that is emancipatory and that rebuilds historical memory, and in a specific case, positioning the singers as political subjects on a nationwide scenario.Thus, the need to consider the so called traditional musics as forms that are not static or homogeneous, on the contrary, they are dynamic, inscribed on complex social processes that not only mould them but with which, on certain cases, they are capable of holding anti-establishment dialogues.
Keywords: alabaos; armed conflict; Chocó; traditional music; rituality.